The Effect of Arm Muscle Strength, Eye-Hand Coordination, Fat Thickness and Self-Confidence on Learning of Batting Cricket Skills - Albert Wolter Aridan Tangkudung; Moch Asmawi; Firmansyah Dlis; James Tangkudung; Sofyan Hanif; Jufrianis Jufrianis (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: The purpose this learning was to determine the direct effect Strength, hand-eye coordination, fat thickness and self-confidence towards batting skills in cricket. . Design/methodology/approach: Research method this learning used quantitative research with technique analysis path analysis approaches. Findings: The population and (total sampling) this learning as 36 athletes regional and national championships PCI (Cricket Association) DKI Jakarta, Indonesia Research limitations/implications: Results of this research: (1) Arm muscle strength has a direct effect on learning y batting cricket athlete PCI DKI Jakarta, coefficient as 0.235 (2) Hand-eye coordination has a direct effect on learning batting cricket athlete PCI DKI Jakarta, coefficient as 0.530. (3) Fat thickness has a direct effect on learning batting Cricket athlete PCI DKI Jakarta, coefficient as 0.029. (4) Self-confident has a direct effect on learning batting Cricket athlete PCI DKI Jakarta, coefficient as 0,259. (5) Arm muscle strength has a direct effect on Self-confident athlete PCI DKI Jakarta, coefficient as 0,280. (6) Hand-eye coordination has a direct effect on Self-confident athlete PCI DKI Jakarta, coefficient as 0,317. (7) Fat thickness has a direct effect on Self-confident athlete PCI DKI Jakarta, coefficient as 0,262. Paper type: This paper can be categorized as a Technical paper